4CPS-246 Palatability assessment of oral medication. (March 2019) - Nisse, Ye; Robert, S; Wicky, J; Henn-Ménétré, S; Demoré, B
Abstract : Background: Some drug forms are not adapted to young children or the elderly. Lists of crushable tablets are already published but do not t consider palatability, which is an additional challenge for drug compliance. Purpose: To determine the palatability of diluted oral solid medications and oral liquid forms. Material and methods: The powder extracted from crushed tablets or opened capsules was diluted in water and flavoured suspending excipient. The minimum solvent needed for dissolution was determined by increments of 1 mL. The solution was then smelled and tasted by three pharmacists to determine the taste and the palatability score (PS) using the 5-point numeric rating scale (1=really bad; 5=really good) of the European Medicines Agency. PS were reported on a visual analogue scale for each drug. The quantity tested by each pharmacist was two drops. The time between two medications was at least 5 min. The possibility of administration of a fraction of the dose was also determined. Modified release formulations and cytotoxic drugs were excluded. Liquid forms were tested with the same method. Results: One-hundred and fifty drugs were tested including 43 liquid forms and 107 solid forms. The average PS was smaller for diluted solid forms than for liquid forms (2.3 vs 2.9, p<0.001). This can be explained by the more frequent bitterness of diluted solid forms (87% vs 14%, p<0.001). PS was less than 3/5 for each tester in 72% of solid forms vs 60% of liquid forms (p<0.001). A dose fraction can be used for 76 diluted solid forms. Flavoured suspending excipient can mask the taste of 80/107 solid medication but only when the bitterness was low. Some medications cause other sensations: tricyclic antidepressants are anaesthetics for mucosa, naftidrofuryl and febuxostat are irritants for esophagus and glycerin in the formulation causes a warm sensation in the mouth. Conclusion: This database provides part of the answer regarding the acceptability of a treatment. PS is an important factor in compliance, particularly in the paediatric population. This method requires to be validated because taste varies with age, ethnic … This study must be completed by other elements such as pH of the solution, stability of the active substance or solubility parameters. References and/or acknowledgements: https://www.ema.europa.eu/documents/presentation/presentation-acceptability-palatability-methods-available-assessment_en.pdf No conflict of interest.